The impact of conditional cash transfers on the matriculation of junior high school students into rural China's high schools. Issue 1 (2nd January 2017) - Li, Fan; Song, Yingquan; Yi, Hongmei; Wei, Jianguo; Zhang, Linxiu; Shi, Yaojiang; Chu, James; Johnson, Natalie; Loyalka, Prashant; Rozelle, Scott
ABSTRACT: The goal of this study is to examine whether promising a conditional cash transfer (conditional on matriculation) at the start of junior high school increases the rate at which disadvantaged students matriculate into high school. Based on a randomised controlled trial (RCT) involving 1418 disadvantaged (economically poor) students in rural China, we find that a CCT voucher has no effect on increasing high school matriculation for the average disadvantaged student. The CCT voucher also has no differential impact on students at any point in the distribution of baseline academic achievement. This result suggests that CCTs, while shown to be effective in many contexts, do not always work.